2012
DOI: 10.1037/a0027410
|View full text |Cite
|
Sign up to set email alerts
|

Can DSM-IV borderline personality disorder be diagnosed via dimensional personality traits? Implications for the DSM-5 personality disorder proposal.

Abstract: The proposal for the diagnosis of personality disorders (PDs) in the Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5; American Psychiatric Association, in preparation) involves, in part, the use of elevated scores on dimensional personality traits. For instance, the diagnosis of borderline personality disorder (BPD) in the DSM-5 will require evidence of self- and interpersonal impairment as well as elevated scores on traits of emotional lability, anxiousness, separation insecurity, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…One possible explanation is that discrepancies reflect fundamental classification and diagnostic issues that have recently been the subject of intense debate in the personality disorder field [46,47]. Categorical diagnoses of PD according to the DSM have come under fire for not fully covering personality pathology, including an arbitrary diagnostic boundary, and being overly heterogeneous [48].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that discrepancies reflect fundamental classification and diagnostic issues that have recently been the subject of intense debate in the personality disorder field [46,47]. Categorical diagnoses of PD according to the DSM have come under fire for not fully covering personality pathology, including an arbitrary diagnostic boundary, and being overly heterogeneous [48].…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence from population and clinical studies supporting the notion that BPD is a dimensional construct, 45 and subthreshold presentations are clinically important. 92 An example of this appears in section 3 of the DSM-5 (conditions that require further research), 1 but at present there is no consensus among the field as to which dimensional model should be adopted.…”
Section: Dimensional Diagnostic Approachmentioning
confidence: 99%
“…43,44 THE DEVELOPMENT OF ADOLESCENT BPD BPD is increasingly seen as a life-span developmental disorder 23 that exists on a dimensional continuum of severity. 45 Despite increasing knowledge of neurobiological and psychosocial risk factors for BPD over the past decade, a detailed understanding of the developmental pathways to BPD has not yet been achieved, and prospective developmental data on adolescent BPD are rare.…”
Section: Psychosocial Functioning and Mental Health Problemsmentioning
confidence: 99%
“…Although Miller and colleagues (2015) recently evaluated the relative associations of Section II and Section III PD constructs and external criterion variables, differential associations specific to BPD conceptualizations and external criteria chosen specifically related to BPD have not been evaluated in previous research. In addition, although previous research has shown that a dimensional measurement of BPD could capture conceptually relevant external criterion variables (Miller et al, 2012)-which indicates some promise of a similar position to Section II BPD within a nomological network for BPD-and that the Section II and Section III operationalizations of BPD are strongly associated with one another Hopwood et al, 2012;Sellbom et al, 2014), research has not yet directly compared these two models and their utility in predicting behavior and associated psychopathology symptoms directly relevant to BPD.…”
Section: Discussionmentioning
confidence: 99%